Endolaparoscopic removal of colonic polyps. (April 2014) - Goh, C.; Burke, J. P.; McNamara, D. A.; Cahill, R. A.; Deasy, J.
Abstract Aim A proportion of colonic polyps is not amenable to exclusively colonoscopic removal due to their location, size or tortuosity of the colon. A combined laparoscopic/colonoscopic polypectomy or endolaparoscopic polypectomy (ELP) is an alternative to formal segmental resection. We present our experience of ELP. Method This is a retrospective review of a consecutive series of patients who underwent ELP for preoperatively diagnosed benign polyps between 2010 and 2013. Data are presented as median (interquartile range, IQR). Results Thirty patients commenced ELP. Eighteen were male and the median (IQR) age was 65.4 (61.6–73.5) years. Of 30 attempted cases, 22 (73%) underwent successful ELP surgery. Patients in whom combined ELP surgery was unsuccessful were converted to laparoscopic colectomy (one) or colonic mobilization and colotomy (seven). The median operation time for successful ELP was 105 (75–125) min. The complication rate was 13.3% and the median length of stay was 2.0 (1.0–3.0) days for successful ELP compared with 5.5 (3.5–6.8) days for converted patients (P = 0.014). The median polyp size was 14 (10–22) mm; eight (26.7%) had high‐grade dysplasia with two cases of invasive cancer identified. Conclusion A combined endoscopic–laparoscopic approach provides an alternative to segmental resection for treating challenging colonic polyps. This approach appears to be safe and effective and should be offered to selected patients with benign colonic polyps.